(NsTARYE MASTERA OPERETTY(B.s (NiSTORIQs - (No(B. (Np(B. (NgREKOWA(B- (NdA[KOWSKAQs ((NmOSKWA s (NiSKUSSTWOs, 1990)
(NwSPOMINAQ STARU@ OPERETTU EE ^ASTO PRENEBREVITELXNO NAZYWA@TIOPERETKOJ(B.s
Keywords: (NISTORIQs